Online news media reports on empirical business research: An exploratory thematic analysis in the knowledge mobilization of business information. (March 2019) - Berry, Alison; Simmons, Shawna
This study explored how empirical business research is translated into business information for professional use within online news media reports. A hybrid approach to thematic analysis was utilized to investigate a sample of new media reports ( N = 53) on recent business research. The analysis revealed that the news media reports generally (1) contained informational categories pertaining to those typically detailed in social-scientific research and (2) utilized either a negative or positive frame for communicating research results. The results of this study reinforce the conceptualization of news media outlets as an intermediary in knowledge mobilization of business information. Additionally, the results of this study identify communicative strategies utilized in news media reports on business research that may allow business information creators to understand how research may be conveyed to knowledge managers and practitioners.